Do paralympic track and field athletes have low energy availability? - Paduan Joaquim, D.; Ridel Juzwiak, C.; Winckler, C. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2018)
One of the greatest challenges when working with athletes is to achieve the energy demands for physiological processes and exercise expenditure. The aim of this study was to assess the energy availability (EA) of Paralympic track and field athletes (sprinters). Seventeen athletes (9 male and 8 female) with visual impairment (VI, n=10), cerebral palsy (CP, n=4) and limb deficiency (LD, n=3) were assessed for energy intake (EI) (4-day food photographic record), energy expenditure with exercise (EEex) (motion sensor), and body composition (skinfolds method). Energy availability was estimated using the equation: EA = (EIkcal - EEexkcal) / fat-free mass (FFM) / day, and values = 30kcal/kgFFM/day were considered as low energy availability (LEA). EEex varied from 130 to 477kcal/h and athletes trained in average for 3.2 hours per day. Mean EA for VI, LD and CP were 36 (2.19), 37 (1.90) and 38 (3.38) kcal/kgFFM/day, respectively. Most (82.3%) participants presented EA below = 45kcal/kgFFM/day, throughout the days, which are the recommended values for athletes without disability. Athletes should be encouraged to consume adequate EA to avoid consequences related to low energy availability. There is need of further research to identify cut-off values adequate for this population.